Testing the twin deficit hypothesis for resource-rich economies in the era ofclimate change - Gurbanov, Sarvar; Nadirov, Orkhan; Gasimova, Samira; Mukhtarov, Elmir; Dehning, Brucue (Routledge, Taylor & Francis Group, 2023)
Burning fossil fuels emits greenhouse gases, the primary culprit of human-induced global warmingand climate change. It is appropriate to revisit the twin deficit hypothesis with an extended data setand increasing evidence on the gravity of climate change. This study tests the twin deficithypothesis for 18 resource-rich countries by employing annual data from 1991 to 2020.Employing panel unit-root tests, specifically, using an extension of the Granger causality test forheterogeneous panels, the findings of this study show that causality runs from the current accountbalance to the fiscal balance for 18 resource-rich countries. However, the sequential panel selectionapproach (SPSM) indicates that the stationarity of the current account balance (or budget balance)in a select few countries, including Equatorial Guinea, Kuwait, Iran, and the United Arab Emirates, isthe only reason why the unit root null was rejected. We have discovered a bidirectional link forthese four resource-rich nations, partially confirming our main hypothesis. This prompts us to testeach of the four countries separately, and only the United Arab Emirates concurs with our primaryclaim. This unidirectional causality from the current account deficit to the budget deficit has policyimplications for the United Arab Emirates.
Keywords: Climate change -- Economic aspects.; Global warming -- Economic aspects.; Fossil fuels -- Environmental aspects.; Fiscal policy -- Resource-rich countries.; Budget deficits -- Developing countries.; Current account -- Developing countries.